Cholesterol as an Endogenous ERRα Agonist: A New Perspective to Cancer Treatment - Casaburi, Ivan; Chimento, Adele; De Luca, Arianna; Nocito, Marta; Sculco, Sara; Avena, Paola; Trotta, Francesca; Rago, Vittoria; Sirianni, Rosa; Pezzi, Vincenzo (Frontiers in Endocrinology, 2018)
The estrogen-related receptors (ERRs) are important members of nuclear receptors which contain three isoforms (α, β, and γ). ERRα is the best-characterized isoform expressed mainly in high-demand energy tissues where it preferentially works in association with the peroxisome proliferator-activated receptor-γ receptor (PPARγ) co-activator 1α (PGC1α) and PGC1β. ERRα together with its cofactors modulates cellular metabolism, supports the growth of rapidly dividing cells, directs metabolic programs required for cell differentiation and maintains cellular energy homeostasis in differentiated cells. In cancer cells, the functional association between ERRα and PGC-1s is further influenced by oncogenic signals and induces metabolic programs favoring cell growth and proliferation as well as tumor progression. Recently, cholesterol has been identified as a natural ERRα ligand using a combined biochemical strategy. This new finding highlighted some important physiological aspects related to the use of cholesterol-lowering drugs such as statins and bisphosphonates. Even more meaningful is the link between increased cholesterol levels and certain cancer phenotypes characterized by an overexpressed ERRα such as mammary, prostatic and colorectal cancers, where the metabolic adaptation affects many cancer processes. Moreover, high-energy demanding cancer-related processes are strictly related to the cross-talk between tumor cells and some key players of tumor microenvironment, such as tumor-associated macrophage that fuels cancer progression. Some evidences suggest that high cholesterol content and ERRα activity favors the inflammatory environment by the production of different cytokines. In this review, starting from the most recent observations on the physiological role of the new signaling induced by the natural ligand of ERRα, we offered a new hypothesis on the suitability to control cholesterol levels as chance in modulating ERRα activity in those tumors in which its expression and activity are increased.